Diffuse intrapulmonary malignant mesothelioma presenting with miliary pulmonary nodules: A case report. (11th March 2015) - Hida, Tomoyuki; Hamasaki, Makoto; Matsumoto, Shinji; Abe, Sosei; Takakura, Koji; Hiroshima, Kenzo; Nabeshima, Kazuki
<x xml:space="preserve">Abstract</x> A 67‐year‐old male with a history of asbestos exposure presented with fever, cough, and dyspnea and was found to have diffuse granular shadowing in both lungs, right pleural effusion, and hilar and mediastinal lymphadenopathy upon chest computed tomography. For definitive diagnosis, a thoracoscopic lung biopsy was performed. Intraoperative findings showed no remarkable macroscopic changes in the visceral and parietal pleura, although a high level of hyaluronic acid in the pleural effusion was noted. Histological findings showed proliferation of atypical cells with round‐to‐oval nuclei, prominent nucleoli, and eosinophilic cytoplasms. These cells were arranged into sheets or tubules and were located predominantly in the lung parenchyma. Lymphovascular invasion was conspicuous. Immunohistochemically, tumor cells were positive for calretinin, D2‐40, and CK5/6, focally positive for Ber‐EP4, but negative for WT‐1, TTF‐1, CEA, and MOC31. Fluorescence in situ hybridization for the tumor suppressor p16 revealed homozygous deletion in the tumor cells. Therefore, we diagnosed the tumor as diffuse intrapulmonary malignant mesothelioma (DIMM). The patient had a poor response to chemotherapy and died 1 year after diagnosis. Although rare, DIMM should be considered when patients present with multiple, tiny intrapulmonary nodules, regardless of macroscopic pleural changes. Furthermore, this is the first report on p16 status in DIMM.